Larvicidal Activity of Ethanol Extracts of Bidara (Ziziphus mauritiana) Leaves and Fruits Against Aedes aegypti - Rochmadina Suci Bestari; Muhammad Ihsanul Fikri; Riandini Aisyah; Metana Puspitasari; Sri Wahyuni; Mitoriana Porusia (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Dengue fever vector control uses abate chemicals can harm the ecosystem. One of the plants that can be used as a natural larvicide is bidara. Bidara leaves and fruits easily available and contains flavonoids, saponins, alkaloids, and tannins. The compound have an impact on the mortality of Aedes aegypti mosquito larvae. Contains study design, subject, methods, data collection and data analysis. Research on ethanol extract of bidara leaves and bidara fruit with Poly Ethylene Glycol (PEG) was experimental laboratory design with post-test only controlled group design. The technique of extraction is maseration. The larvae of Aedes aegypti instar III-IV are used, 800 in total, divided into 8 groups. At 6, 12, 18, and 24 hours, the number of dead larvae was counted .Normality and homegenity tests obtained the results of data not normally distributed and not homogeneous, so it is necessary to do the Kruskall-Wallis non-parametric test followed by Mann-Whitney post hoc .The result is bidara leaf extract with a concentration of 1.5% + 3% PEG resulted in 100% larval death in the 24th hour, meanwhile bidara fruit extract with concentration of 1.5% + 3% PEG resulted 70% larval death in 24th hour. Ethanol extract of bidara leaves has better effectiveness than bidara fruit extract in its ability as a larvicide, where bidara leaf extract with a concentration of 1.5% + 3% PEG resulted in 100% larval death in the 24th hour.